APLIKASI SURABAYA HERITAGE BERBASIS WEBSITE - Handojo, Andreas; Lim, Resmana; Christian, Robby; Gosal, Robert; Bastion, Yulius (Jurnal Informatika, 2015)
Utilization of communication and computer technology has spread into various fields. Begin from the world of entertainment, education, business, health, life-style, and also the tourist field. Nowadays, still lack of the information related to the city of Surabaya as historical information, information about tourist sites, and others. This research conduct to develop an application to explore the history of the city of Surabaya as historic sites, tourist sites, museums, and the event agenda in town. With this application, the user is expected to be able to learn about the history of the city of Surabaya in the interesting form by combining text, picture, sound, and Google map facilities, as well as well as the promotion of tourism and events agenda are hosted in the city of Surabaya. Surabaya Heritage Applications created on a web-based application that is intended for public to know better about the history, tourism objects, as well as the event agenda in the city of Surabaya. Based from the testing results, the application was able to perform functions such as pre-planned. Meanwhile, testing by sampling questionnaires to the user produce that the application is attracting interest from users by 85%. It can be concluded that the applications made quite meet the target research.